JK ROWLING’S THE TALES OF BEEDLE THE BARD: A MAGICAL REALISM ANALYSIS - Agung Kusuma (English Letter Department, Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2019)
Literature plays an important role in psychological and social development of a child. Literature stimulates children’s imagination and sharpens their awareness of the world around them. It teaches our children about values, norms, equity, and firmly establishes the qualities of tolerance, compassion, sharing, caring, and ability to solve conflict. Therefore, it is undeniably important to shed a light on what our children read as they will project what they read in stories through their behavior. Using a post-colonial discourse, the writer put forward a well elaborate analysis and findings of magical realism study on JK Rowling’s short stories The Tales of Beedle the Bard. Moreover, the analysis focuses on how magical object describing the magical realism aspects is depicted as a part of human life and how it brings affects for the child readers.